Association of interleukin-6 and C-reactive protein with in-hospital mortality in patients with ST-elevation myocardial infarction undergoing primary percutaneous coronary intervention - Rachman, Adelia U.; Saputra, Firandi; Bagaswoto, Hendry P.; Setianto, Budi Y. (Narra J, 2026)
Inflammation contributes substantially to the pathogenesis of acute coronary syndromes (ACS), and interleukin-6 (IL-6) and C-reactive protein (CRP) have been proposed as biomarkers of adverse outcomes. The aim of this study was to evaluate the associations of IL-6 and CRP with in-hospital mortality among patients with ST-elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI). This prospective cohort study enrolled adult patients with STEMI who underwent primary PCI at Dr. Sardjito General Hospital, Yogyakarta, Indonesia, in 2023. A single blood sample for IL-6 and CRP measurement was collected within 24 hours after PCI. In-hospital mortality was recorded during hospitalization. Receiver operating characteristic analysis identified optimal cut-off values, and multivariable logistic regression was performed to adjust for potential confounders. In-hospital mortality occurred in 6 patients (12.8%). In univariate analysis, higher IL-6 and CRP levels were associated with in-hospital mortality. IL-6 ≥84.60 pg/mL showed an area under the curve (AUC) of 0.776, sensitivity of 66.7%, and specificity of 82.9% (p=0.007), whereas CRP ≥31.35 mg/L showed an AUC of 0.748, sensitivity of 83.3%, and specificity of 68.3% (p=0.015). However, after adjustment for confounding variables in separate multivariable models, neither IL-6 nor CRP remained independently associated with in-hospital mortality. These findings indicate that although elevated IL-6 and CRP levels were associated with in-hospital mortality in unadjusted analyses, their independent prognostic value was not retained after accounting for other clinical and laboratory factors. Further studies with larger sample sizes are needed to clarify the role of these inflammatory biomarkers in risk stratification among patients with STEMI.